Validity and reliability of the Turkish version of the transition of primiparas becoming mothers scale - Zila Özlem Kirbaş; Elif Odabaşi Aktaş; Hava Özkan (BMC, 2024)
Abstract Background The transition to motherhood is an important life event in a woman's life and represents an important developmental process that brings physical, psychological and social changes to gain a new role. However, research on the transition to motherhood in Turkish society is scarce. There is a need for a comprehensive, practical and reliable tool to evaluate the transition to motherhood in primiparous mothers. This study evaluated the reliability and validity of the Turkish version of the Transition of Primiparous Becoming Mothers Scale (TMP-S) to evaluate the transition process of primiparous mothers to motherhood. Methods This methodological research was carried out in obstetrics and gynecology outpatient clinics, pediatric outpatient clinics, and family health centers of a hospital in Türkiye. The sample consisted of primiparous mothers of 0 to 6- month-old babies who visited clinics and family health centers for routine postnatal examinations (n ​​= 305). After evaluating the language equivalence and content validity of the scale, test-retest reliability, internal consistency and construct validity were examined. Factor analysis, Pearson's correlation, retest reliability, and Cronbach's alpha were employed to evaluate structural validity and reliability. Results The final TPM-S had two dimensions with 25 items. Exploratory factor analysis revealed a two-factor solution, which accounted for 59.276% of the variance. Confirmatory factor analysis showed that the model fit of the two-factor model also reached a satisfactory model ft after modification. The comparative fit index was 0.894, the Tucker‒Lewis index was 0.882, and the root mean square error of approximation was 0.079. The content validity index of the scale ranged from 0.56 ~ 0.77. The Cronbach's alpha coefficient was 0.93 for the total scale, and the test-retest reliability was 0.96. Conclusions It is a valid and reliable tool for evaluating the transition to motherhood among primiparous mothers of 0 to 6 month-old babies in Türkiye. Turkish researchers and healthcare professionals can routinely apply this measurement tool to primiparous mothers in the first six months after birth to evaluate their transition to motherhood.